Teacher training: The challenge of practice (Research, Society and Development, 2021)
This article is a master's research for the Program PPGen UNIC/IFMT, which sought to investigate whether qualification in teacher education has reached the expected proportion for improving student learning. Therefore, a case study was proposed, with an interview script conducted with 15 teachers in a Public School of the Municipal Education Network EMEB Osmar José do Carmo Cabral that serves a total of 670 students and aimed to identify the importance of educational praxis in the process of development and learning of students and to reflect on the multiple languages that constitute the universe of continuous self-training of education professionals in the school environment. At a certain point, it is justified that this study is necessary for teachers to recognize and use training to subsidize teaching, using them as a very important ally in the construction of knowledge. In the methodology of this work, a qualitative methodological approach was proposed for data analysis and interpretation. From the partial results, the research highlights the importance of training; however, it is necessary that the teaching work is an updating instrument aimed at pedagogical practice in order to contribute to the improvement of student learning.